Impact of resident standardized training satisfaction and perceived organizational support on career commitment: a study of teachers of resident standardized training in China - Zeng, W. L.; Ma, S.; Yu, Z. G.; Zhao, Y. W. (Chinese Hospitals, 2018)
Objectives: To understand the status quo of the on satisfaction and organization support and career commitment of resident standardized training teachers on in China, compare the gaps of teacher’s different personality on those of factors, analyze the impact of satisfaction and organization support of resident standardized training on career commitment and give some reference on continuous promoting resident standardized training system in China. Methods: Teachers who participated the 2017 Summit Forum of China’s National Standardized Training for Resident Doctors were selected to have an online questionnaire. Results: The investigated has high levels of job satisfaction, perceived organizational support and career commitment. Their job satisfaction and perceived organizational support has significant positive effect on the career commitment. There are some differences among teachers personality characters on the impacts of job satisfaction, organization support and career commitments. Conclusions: It is considered to establish a standardized system for admittance of qualified teacher, improve the motivation mechanism and improve career commitment to assure the quality of resident standardized training in China.